-6(7v-5)-3=3(v-6)

Simple and best practice solution for -6(7v-5)-3=3(v-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(7v-5)-3=3(v-6) equation:


-6(7v-5)-3=3(v-6)

We simplify the equation to the form, which is simple to understand
-6(7v-5)-3=3(v-6)

Reorder the terms in parentheses
+(-42v+30)-3=3*(v-6)

Remove unnecessary parentheses
-42v+30-3=+3+*(+v-6+)

Reorder the terms in parentheses
-42v+30-3=+(+3v-18)

Remove unnecessary parentheses
-42v+30-3=+3v-18

We move all terms containing v to the left and all other terms to the right.
-42v-3v=-18-30+3

We simplify left and right side of the equation.
-45v=-45

We divide both sides of the equation by -45 to get v.
v=1

See similar equations:

| -17=19-12m | | 4x+6=5x-12 | | X+4.5=8.7 | | 0.2x+3=28 | | 1.3+x=-1.6 | | V+6=-12 | | S=52+2.75p | | -1+3(x+2)=5(1+8x) | | -(2y-12+(-y))=-33 | | Y^4+y^3-4y-16=0 | | 5x+12=108-10x | | 1.3+-1.6= | | (4x)-(3x)+(2x)=24 | | 9+2j=5 | | 8m=7(7x-1) | | 18.84=2(3.14) | | 0.3(32)+x=0.3(20+x) | | 11x+45=2x | | (5-6i)(3-2i)=0 | | 3q+10=7 | | 7-(6x+2)=(x-12)+3 | | 2a+9=5a-6 | | x=18-2/3 | | 6+x=54 | | 67-39= | | 9.4=x-17 | | 2a+9=5a+6 | | .05x+.10(19-x)=1.55 | | 27=.9(200-a) | | 2x+3m-5x+7m= | | -3y-9=6y+18 | | x-11+-7= |

Equations solver categories